Leading your research team in science - Jansen, Ritsert C. (Cambridge : Cambridge University Press, 2019)
Team leaders should be full of ideas for new research projects and inspire a research group to achieve great results. This practical guide for team leaders, and those who aspire to become team leader, offers a unique approach to help readers develop research and become a more independent and productive investigator. Readers can learn how to recruit and develop talented team members, how to negotiate contracts and manage projects, and how to create wider visibility and publicity for their science. From human resources and project finances, legal affairs and knowledge transfer to public engagement and media performance, the book provides guidance to enhance skills and combine them with those of support staff on the road to success. With numerous valuable tips, real-life stories and practical exercises, this must-read guide provides everything needed to take responsibility for leading research teams. This title is available as Open Access via Cambridge Core.
Contents -- Introduction -- Team -- Introduction -- Scout -- Select -- Prepare -- Advance -- Organization -- Introduction -- Human resources -- Financial affairs -- Legal affairs -- Patent affairs -- Society -- Introduction -- Open science -- Citizen science -- Media -- Web profile -- Epilogue -- Further reading -- Acknowledgements.
Title from publisher's bibliographic system (viewed on 11 Dec 2018).
Keywords: Science -- Methodology; Science projects